The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1093/cercor/bht050
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Range Fronto-Parietal 5- to 10-Hz Network Predicts "Top-Down" Controlled Guidance in a Task-Switch Paradigm

Abstract: The capacity to rapidly adjust behavioral strategies according to changing task demands is closely associated with coordinated activity in lateral and medial prefrontal cortices. Subdivisions within prefrontal cortex are implicated to encode attentional task sets and to update changing task rules, particularly when changing task demands require top-down control. Here, we tested whether these top-down processes precede stimulus processing and constitute a preparatory attentional state that functionally couples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
85
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 92 publications
(150 reference statements)
8
85
0
Order By: Relevance
“…Our main finding characterized the statistical relation of two band-limited activity fluctuations comprising a narrow ∼5-to 10-Hz (peak at 7 Hz) theta band and a ∼35-to 55-Hz (peak at 40 Hz) gamma band. Previous studies have documented that a 5-to 10-Hz theta band is a widespread LFP signature in ACC/PFC that increases with specific demands to control goal-directed behavior (22)(23)(24)(25). Our study corroborates these reports (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Our main finding characterized the statistical relation of two band-limited activity fluctuations comprising a narrow ∼5-to 10-Hz (peak at 7 Hz) theta band and a ∼35-to 55-Hz (peak at 40 Hz) gamma band. Previous studies have documented that a 5-to 10-Hz theta band is a widespread LFP signature in ACC/PFC that increases with specific demands to control goal-directed behavior (22)(23)(24)(25). Our study corroborates these reports (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Our data extend these findings by showing that the peak frequencies of corticostriatal theta and gamma oscillations scale with movement speed. This suggests that theta and gamma oscillations are also involved in corticostriatal processing in the most basic functional domain of the corticobasal ganglia system, motor behavior (Marsden, 1982;Phillips et al, 1993;Mink, 1996;Turner and Desmurget, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The striatum is the main input structure of the basal ganglia (Alexander et al, 1986;Parent and Hazrati, 1995) and is thought to be involved in reinforcement learning and procedural memory (Bar-Gad et al, 2003;Schultz et al, 2003;Yin and Knowlton, 2006). Furthermore, the striatum also has an important role in motor behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, White et al (2013) concluded that in their fMRI-EEG study "it is likely that the frontal theta recorded currently has a medial frontal DMN [default mode network] source" (p. 2940; see also Michels et al, 2010 for a similar conclusion). Phillips et al (2014) provided direct evidence in the macaque for a role of theta-band oscillations in cognitive control, with a medial frontal source. It is unclear why the increased theta power recorded with EEG should be accompanied by reduced BOLD signal recorded with fMRI, but one possibility, supported by both theoretical and empirical arguments, is that periods of increased theta power may be accompanied by a decrease in power in higher frequencies such as gamma, and hence a net reduction in metabolic demand (Hsieh & Ranganath, 2014;Kilner et al, 2005).…”
Section: Introductionmentioning
confidence: 97%